"A chiare lettere - Confronti” • A proposito di guerra o pace ai tribunali ecclesiastici esistenti in Italia. Quale cultura di riforme organiche sta dietro l’attuale pontificato? (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO. 1. Preambolo: perseverare diabolicum? - 2. (segue) I tribunali regionali nella attuazione del regime concordatario, in Italia - 3. Ancora in tema di competenza matrimoniale dell’ordinario diocesano. Intermezzo - 4. Corollari di principio in tema di giurisdizione penale e/o amministrativa - 5. Problematicità di una transizione contraddittoria, a ogni livello - 6. (segue) Dalla frammentazione feudale all’armonia di un moderno ordinamento giudiziario.Regarding peace of war to the italian ecclesiastical courts. Which is the methodical reform background of pope Francis?ABSTRACT: The accentuated tendency of the part of the Vatican (MP Mitis judex) to express a preference for the pastoral attributions of the diocesan bishop in terms of judgment of nullity of canonical marriage, in competition with those of the interdiocesan ecclesiastical tribunals created for the implementation of the concordat regime in Italy (MP Qua cura), could propose in this matter, after the Gospodinoff case (Constitutional Court, dec. N. 1/77) and the Pellegrini case (European Court of Human Rights, sentence 20 July 2001), the risk of a further vulnus to the principles of due process, on the other hand recently renforced in the Italian constitutional order. In dwelling on this inconvenience, the Author observes that the Catholic Church expresses with this, once again, its serious cultural and political delay in relation to the modern systems with which interacts ; and wonders why the Holy See has not decided by now to abandon the institutes and doctrines of ecclesiastical public law with which, starting from the 16th-17th centuries, with intransigence worthy of the better cause is has too often continued to feed the claim to keep on regulate relations with the political authorities on the models , now obsolete and perishable, of the Christian regime. The Author takes the opportunity to indicate how, conversely, the model of the interdiocesan tribunals, even if imperfect, can and should be generalized, in order to begin to solve the set of problems that the lack of modernization of the canonical system proposes, on the subject of the judicial system, in comparison with the level of refinement reached by legislative policy and the science of law (at the state and interstate level), in terms of protection of human rights, in the field of administrative and criminal procedural law.